The role of translational medicine in infectious diseases (Actualizaciones en Sida e Infectología, 2023)
The term translational medicine was coined about twenty years ago, in 2003, when the U.S. National Institutes of Health (NIH) launched their “road map” for future research. In this road map, the NIH prioritized the human genome sequence, with the clear message of transforming the existing clinical research systems and direct efforts towards discoveries that benefitted people’s health and quality of life in a shorter time than usual. Translational medicine combines basic or biomedical research findings with clinical practice, to accelerate research processes seeking to solve health problems that focus on diseases requiring a diagnosis, a treatment, or prevention strategies (1). The study of molecular and cellular mechanisms underlying disease, including infectious diseases, and the close collaboration between base scientists, clinical researchers, members of the health team, decision-makers, and businesspeople seeks to boost the development of innovative responses as well as improve the understanding of pathogenic processes to optimize the prevention, diagnosis, and treatment of disease in the era of human genome. Thinking in terms of translational medicine is acknowledging that progress in basic science increasingly contributes information on pathogenicity mechanisms, genetic and hereditary bases, infection transmission, and host adaptation from the sequencing of bacterial and viral genomes. Quoting Andrea Gamarnik, “if we know the changes we can make at molecular level so that dengue virus type 2 (DEN) cannot counter the immune system action, we will be able to design better vaccines through genetic engineering”, and she adds “...in our work, we find that by just changing one amino acid in the NS5 protein of DEN2 (equal to taking out a brick from the whole building of the viral protein), we can simulate what happens in DEN4 and with this information we could obtain better vaccines...” (2). Globally, it is estimated that around 75% of the new infectious diseases affecting humans that were discovered in the last 10 years have originated in animals (3). This information, together with the need to tackle resistance to antibiotics, promote innovation in vaccines, prepare for the appearance of new zoonoses, and integrate research approaches in humans and animals, generated the One Health initiative (4). It consists in a translational, integrated, and unifying approach for the purpose of balancing and optimizing people, animal, and ecosystem health in a sustainable way. The approach that mobilizes multiple sectors, disciplines, and communities at different levels in society uses translational research to work together, promote wellbeing, and tackle any threats to health and ecosystems (5). In the last decades, Argentina has doubled its efforts to develop translational medicine, which requires a better exchange of knowledge and skills between academia, industry, and the government. This development had a positive turning point at the beginning of the COVID-19 pandemic, when the Coronavirus Unit was jointly created by CONICET and I+D+I Agency. In previous years, however, the Ministry of Science and Technology promoted the development of technological projects and invested in the human resources, infrastructure, and equipment required for translational research in hospitals through calls for Biotechnological Projects on Translational Research in Health (PBIT, in Spanish). One example is the creation, in 2017, of a biobank for infectious diseases within the Instituto de Investigaciones Biomédicas en Retrovirus y Sida (INBIRS) of the University of Buenos Aires and CONICET (5). Moreover, the Ministry of Health, pursuant to Resolution 2060/2020, launched the National PlanforTranslationalResearchinHealthfortheHospital Network, which includes the creation of Translational Knowledge Hospital Units (UCT-Hospitalarias, in Spanish). Finally, CONICET created the Network for Translational Research in Health (Red de Investigación Traslacional en Salud, RITS), a joint initiative of various institutions involved in applied research in the field of human health. RITS promotes collaborative networking to solve difficulties that arise when implementing research results and to promote research itself as a result of institutional collaboration. Among the ad hoc teams, the infectious disease modeling group (6) studies the dynamics of infectious disease transmission as complex systems that cannot be understood from one single discipline or by merely overlapping disciplines; that is, it requires dialog and common grounds for understanding. In conclusion, translational medicine requires special attention from scientists and health teams in many topics. The key is collaborative and transdisciplinary work, which implies a process of integrating the disciplines by following the opposite path to that of specializing in separate knowledge and poorly connected watertight compartments. In conclusion, translational medicine requires special attention from scientists and health teams in many topics. The key is collaborative and transdisciplinary work,
Keywords: translational medicine; infectious diseases